2005
DOI: 10.1080/00015550510030069
|View full text |Cite
|
Sign up to set email alerts
|

Density of Demodex folliculorum in Perioral Dermatitis

Abstract: The role of Demodex folliculorum in perioral dermatitis is not satisfactory explained. Our purpose was to assess the density of D. folliculorum in perioral dermatitis and evaluate the relationship of the mite count to previous therapy with topical steroids. A standardized skin surface biopsy of the chin was performed in 82 female patients with perioral dermatitis and in 70 control female subjects. Patients who received previous topical steroid therapy had a significantly higher mite density than the patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 32 publications
(39 reference statements)
4
42
0
3
Order By: Relevance
“…That finding was confirmed by the present study (OR=8.1). The hypothesis that SID and Seb D were associated with Demodex mites has not been confirmed at present, but our results were consistent with those of Dolenc-Voljc et al (2005) and Karincaoglu et al (2008;.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…That finding was confirmed by the present study (OR=8.1). The hypothesis that SID and Seb D were associated with Demodex mites has not been confirmed at present, but our results were consistent with those of Dolenc-Voljc et al (2005) and Karincaoglu et al (2008;.…”
Section: Discussionsupporting
confidence: 82%
“…Demodex mites are usually considered to play a pathogenic role when present in an excessive number or penetrating into the dermis (Ayres and Ayres, 1961;Ecker and Winkelmann, 1979;Bonnar et al, 1993;Forton and Seys, 1993;Erbagci and Ozgoztasi, 1998). They have been implicated in the occurrence of a wide range of clinical features, including pityriasis folliculorum (Ayres and Ayres, 1961), papulopustular and granulomatous rosacea (Bonnar et al, 1993;Forton and Seys, 1993), inflammatory papule (Seifert, 1978), folliculitis (Purcell et al, 1986), seborrheic dermatitis (Karincaoglu et al, 2009), perioral dermatitis (Dolenc-Voljc et al, 2005), and blepharitis (Post and Juhlin, 1963;Zhao et al, 2011a), although much controversy persists (Bonnar et al, 1993;Forton and Seys, 1993;Forton et al, 2005;Hsu et al, 2009). A definitive diagnosis of demodicosis requires a compatible clinical picture and the presence of more than 5 mites/cm 2 (Forton and Seys, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of Demodex mites seem to be harmless residents of the skin; however, the presence of larger-than-normal numbers of Demodex mites has been suggested to be pathogenic. D. folliculorum has been incriminated as playing a role in the development of clinical dermatological conditions such as rosacea, granulomatus perioral dermatitis, blepharitis, pityriasis folliculorum and pustular folliculitis, although much controversy persists (English and Nutting 1981;Gutgesell et al 1982;Clifford and Fulk 1990;Corredor-Osorio et al 2000;Dolenc-Volje et al 2005;Elston 2005Elston , 2010Kligman and Christensen 2011;Lacey et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that the pathogenicity of Demodex is related to population. In humans, the association between D. folliculorum and pityriasis folliculorum, rosacea, perioral dermatitis, and blepharitis is stronger than that between D. brevis and those diseases (Ayres and Ayres 1961;Forton and Seys 1993;Dolenc-Voljc et al 2005). However, in dog, whether Demodex injai or D. canis is pathogenetic remains controversial (Hillier and Desch 2002;Sastre et al 2013).…”
Section: Discussionmentioning
confidence: 95%